ANALYSIS OF THE USE OF ACCOUNTING BASE ON VILLAGE GOVERNMENT ENTITIES - Deni - Herdiyana (Politeknik Negeri Semarang, 2019)
The aim of this study is to identify the accounting base that is the most appropriate to be applied by the Village Government in the framework of managing and reporting the Village Fund transparency and accountability. The study was conducted through the desk study approach and analysis of journals related to the application of an accounting basis for Government Accounting Standards (SAP). The results of the study showed that the basis of Cash toward Accrual (CTA) is the best applied by the Village Government since the presentation of financial information is more complete than the Cash basis and meets the principles of transparency and accountability. Furthermore, the application of the CTA basis does not incur high costs such as the application of an Accrual basis. Regarding the application of the village reporting accounting system based on CTA, the researcher proposes the need for technical guidance and / or socialization before the adoption of CTA basis so that there are no constraints when applying this CTA basis